(untitled) (diségno, 2024)
A reading of the European Landscape Convention, combined with an analysis of European guidelines on education for cultural heritage and sustainability, underlines the importance of developing pathways that connect communities with landscapes, link schools with their surrounding areas and engage young people in practices that promote active, responsible citizenship. The aim is to involve them directly in formulating and pursuing goals related to understanding and caring for their local landscapes. This reflection originates from a European project involving universities, art-based research centres, local associations and primary and secondary schools in Italy, Spain and Austria. Teachers, researchers and local stakeholders travelled across Europe to share knowledge and experiences, co-design teaching methods and field-test them in both ordinary and fragile contexts. The study thereby developed a set of practices focused on raising awareness, promoting and communicating the landscape, aimed at highlighting its various elements –both tangible and intangible– and their multiple representations. The paper analyses the results of the research, in particular a MOOC (Massive Open Online Course) designed to equip educators with theoretical foundations, methodological insights and best practices for landscape education, understood as cultural heritage and a key resource for sustainable development.